Origami: History, folds, bases and napkins in the art of folding - Reis, J. (Architecture In-Play International Conferences Proceedings 2016, 2016)
Origami is an ancient art of paper folding, existing since the invention of paper. Pure traditional origami consists on performing a series of folding operations on a square sheet of paper to assemble a final paper model. This paper is basically an introduction to origami and it is composed of a brief introduction and history of this ancient art followed by three essentially demonstrative sections. The first of these sections shows the basic folds, which are the essential steps used in origami making: the valley/mountain, pleat, crimp, reverse, sink, squash, swivel, rabbit ear and petal folds are shown. The second section shows some of the standard bases. Bases are essentially incomplete origami models, used as halfway baselines to produce different finished models: the kite, fish, bird, frog, cupboard, windmill, water bomb, square and blintz bases are shown. Finally, there is a third section showing some popular napkin origami models. A final conclusion with our intentions for future work will terminate the paper.